The Relationship Between Mastery of Novel Theory and the Ability to Appreciate the Elements of the Synopsis in Tere Liye’s Rembulan Tenggelam di Wajahmu Among 10th Grade Students at SMA Negeri 2 Siborongborong in the 2023/2024 Academic Year: Hubungan Penguasaan Teori Novel dengan Kemampuan Mengapresiasi Unsur-Unsur Sinopsis Novel Rembulan Tenggelam di Wajahmu Karya Tere Liye di Kalangan Siswa Kelas X SMA Negeri 2 Siborongborong Tahun Pelajaran 2017/2018 - Masnaria Pasaribu; Ipan Sihite (Boraspati Journal: Journal of Bilingualism, Organization, Research, Articles, Studies in Pedagogy, Anthropology, Theory, and Indigenous Cultures, 2025)
This study aims to analyze the relationship between students' mastery of novel theory and their ability to appreciate the intrinsic elements of the synopsis of Rembulan Tenggelam di Wajahmu, a novel by Tere Liye, among tenth-grade students at SMA Negeri 2 Siborongborong in the 2023/2024 academic year. This research employs a correlational survey method, with data collected through multiple-choice objective tests. The sample consists of 40 randomly selected students. The results indicate a significant correlation between students' mastery of novel theory and their ability to appreciate the intrinsic elements of a novel synopsis. The findings suggest that the higher a student understands novel theory, the better their literary appreciation skills. This study's implications can serve as a reference for improving literature learning in schools, particularly in enhancing students' appreciation of literary works through a theoretical understanding.